2021
DOI: 10.3390/rs13152889
|View full text |Cite
|
Sign up to set email alerts
|

Sino–EU Earth Observation Data to Support the Monitoring and Management of Agricultural Resources

Abstract: Novel approaches and algorithms to estimate crop physiological processes from Earth Observation (EO) data are essential to develop more sustainable management practices in agricultural systems. Within this context, this paper presents the results of different research activities carried out within the ESA-MOST Dragon 4 programme. The paper encompasses two research avenues: (a) the retrieval of biophysical variables of crops and yield prediction; and (b) food security related to different crop management strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Our result confirms that including water balance in the SAFY model is unnecessary as long as ELUE is calibrated with EO-derived LAI [19,36]. However, stress factors during the grain filling stage, such as high temperature, pests, and disease, could also lead to discrepancies between calibration and yield prediction accuracy [44]. Thus, joint assimilation of parameters that determine yield (e.g., soil moisture) and integration of yield in the calibration process could further improve yield prediction, which is worth further investigation.…”
Section: B Spatial Variability Of Yield Estimationsupporting
confidence: 74%
See 1 more Smart Citation
“…Our result confirms that including water balance in the SAFY model is unnecessary as long as ELUE is calibrated with EO-derived LAI [19,36]. However, stress factors during the grain filling stage, such as high temperature, pests, and disease, could also lead to discrepancies between calibration and yield prediction accuracy [44]. Thus, joint assimilation of parameters that determine yield (e.g., soil moisture) and integration of yield in the calibration process could further improve yield prediction, which is worth further investigation.…”
Section: B Spatial Variability Of Yield Estimationsupporting
confidence: 74%
“…Although the calibration accuracy of rice was good, we found a higher DAM and yield error, implying that the fixed parameters influencing biomass and yield portioning (DAM0 and HI) contributed to the error. It was also reported that SAFY performs poorly when yield is greatly limited by stress due to weeds, pests, and diseases [44]. Although weeds are a common problem, the higher sensitivity of rice to weeds than maize could be the second reason for SAFY's low performance in rice.…”
Section: B Crop Yield Estimationmentioning
confidence: 99%
“…Similarly, the data fusion between Landsat and MERIS-FR was performed by Sisheber et al [158], Zurita-Milla et al [159] and Zurita-Milla et al [160] to develop the spatial resolution of MERIS. Pignatti et al [19] developed these methods by analyzing the spatial data of Landsat to improve the MERIS data (Table 2). These data are acquired by classifying the Landsat images to characterize the mixed pixels.…”
Section: Satellitesmentioning
confidence: 99%
“…The LAI is an important index that provides crop growth condition by regulating water and predicting yield [18]. Therefore, accurate estimation of LAI can be used to precisely forecast croprelated factors, such as crop coefficient (kc) and crop yield factor (ky) [19]. The AGB content is strongly correlated with crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Let us briefly explore the main technologies in agriculture, progressing from the top to the bottom. Satellite imagery enables soil classification [9][10][11][12][13][14][15][16][17][18][19][20][21], field monitoring [22][23][24], planning assistance [25], and yield prediction [26][27][28][29]. Open programs are mostly limited-both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%